A new era for public–private partnership (PPPs) in Egypt's urban water supply projects: risk assessment and operating model. Issue 1 (31st December 2022) - Selim, Ahmed M.
ABSTRACT: The UN summit entitled "Transforming Our World: Sustainable Development Plan 2030"considered the provision of clean water and sanitation (Goal no 6) one of the 17 key goals that the UN is striving to achieve. In this respect, Egypt is considered one of the countries that will suffer from water shortage because of establishing the Grand Ethiopian Renaissance Dam (GERD) and tremendous population growth. This research explores the current state of the water supply sector in Egypt based on the distinctive characteristics and challenges facing the development in this sector. Previous literature has examined the key performance indicators (KPIs) for the water supply sector, (PPPs) approach as an effective tool to promote the water supply sector, China's expertise in water supply by PPPsand summarizing the potential multiple risks associated with water supply projects from the literature reviews. Thereafter, an electronic questionnaire was conducted with multidisciplinary experts to identify optimal models (PPPs), weighted for (PPPs) pillars, and assess the potential risks by the Egyptian economy, and social circumstances in the field of water supply. As such, the findings in this research identify and rank the high potential risks based on the opinion of the experts, and an operating model to promote the (PPPs) projects in the water sector in Egypt was proposed based on the identified risk factors (KPIs) and the (PPPs) agreements.